Morphology, thermal and barrier properties of biodegradable films of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) containing cellulose nanocrystals. (February 2017) - Malmir, Sara; Montero, Belén; Rico, Maite; Barral, Luis; Bouza, Rebeca
Abstract: Solvent casting method was used to prepare biodegradable films of poly (3-hydroxybutyrate-co-3-hydroxyvalerate) with cellulose nanocrystals (CNC). Nucleating effect of cellulose nanoparticles was confirmed with DSC and POM tests while WAXS patterns showed that the crystalline structure of bionanocomposites was not changed. POM images showed that smaller spherulites were formed with higher rate and quantity in the samples with CNC compared to neat polymer. TEM images illustrated that CNC nanoparticles were well dispersed in the films up to 4 wt.% of CNC. SEM results exhibited significant reduction in the porosity of the matrix with addition of CNC up to 4 wt.%. More surface roughness for bionanocomposites was observed in AFM images compared to unfilled matrix. Moreover, nanocomposites with 4 wt.% of CNC exhibited better barrier properties against water vapor and oxygen up to approximately four times more than neat PHBV. These biodegradable nanocomposites could be a good alternative for synthetic plastic packaging materials.